An overview of landslide hazard mapping and rating systems in Nepal - Dhital, Megh Raj (Journal of Nepal Geological Society, 2000)
The landslide hazard (LH) maps prepared by various agencies and individuals in Nepal can be classified into the following three types: (1) map of a region. (2) map of a corridor, and (3) map of a site. The regional LH maps include watersheds, sub watersheds, or part of them. These maps are used mainly for watershed management, infrastructure planning, and estimating erosion and sedimentation. The LH maps of a corridor are prepared for the purpose of comparing them with other alternatives, delineating hazardous areas for further studies, and estimating risks in the construction or maintenance of the linear infrastructure in that strip. On the other hand, the LH maps of a specific site are prepared for the purpose of landslide (or slope) monitoring as well as for delineating areas requiring immediate, short-term, or long-term mitigation measures. In Nepal, various rating systems are used for the preparation of LH maps. The number of attributes used for rating varies widely (from 5 to 20). Generally, there are from 3 to 5 subcategories in each attribute. The LH map is prepared by superimposing the rating attributes manually or by the help of a computer. This type of map contains from 3 to 4 hazard categories (i.e. low. medium. high. and very high). The rating system for a regional LH map is developed on the basis of landslide distribution pattern within the subcategory of an attribute. The LH map of a corridor is prepared by dividing it into soil and rock slopes based on the field data, topographical map, and/or aerial photo interpretation. The LH map of a site is prepared on 1:2,000 or larger-scale topographical maps or oblique photomosaic. Some examples of the above three types of LH maps are also given.